META-ANALYSIS OF THE EFFECT OF THE PROJECT-BASED LEARNING MODEL ON SCIENCE LEARNING OUTCOMES AND CREATIVE THINKING SKILLS - Syamsul Bahari (Physics and Science Education Journal (PSEJ), 2025)
This study aims to analyze the effect of the Project-Based Learning (PjBL) model on students’ science learning outcomes. The research employed a literature review method using a meta-analysis approach to synthesize findings from previous empirical studies. A total of 21 journal articles relevant to the implementation of PjBL in science learning were selected as data sources. Data analysis was conducted by calculating effect sizes to determine the magnitude of the impact of the Project-Based Learning model on science learning outcomes. The results of the meta-analysis indicate that the Project-Based Learning model has a significant positive effect on science learning outcomes, with an average effect size of 2.31, which falls into the high-effect category. These findings suggest that PjBL effectively enhances students’ understanding of science concepts by promoting active learning, collaboration, and meaningful engagement with learning materials. Furthermore, the use of project-based activities encourages students to develop creative thinking skills and apply scientific concepts in real-world contexts. In conclusion, the Project-Based Learning model has a strong and significant influence on science learning outcomes and can be recommended as an effective instructional strategy for improving students’ academic achievement and higher-order thinking skills in science education.